Some remarks about the morality of Roman provincial funerary poetry - Fehér, Bence (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The morality/view of life of the ordinary provincial Roman is hard to discern; for the most part we must rely on the more literary inscriptions. The funerary verse inscriptions provide considerable material, but not individualized wording: they consist mostly of well-known patterns. At the same time these patterns form regionally different structure types; hence they can throw light upon the funeral customs of the different regions. In Pannonia there were two main poem types: one of early Carnuntum, and one of Aquincum in the 3rd c. The differences between these communities in the way they thought about death are clearly visible. There were very few individualized poems referring to personal feelings: two such are analysed here in detail (TAq 769, TAq 512).